Task-dependency and structure-dependency in number interference effects in sentence comprehension - Franck, Julie; Colonna, Saveria; Rizzi, Luigi (Frontiers in Psychology, 2015)
We report three experiments on French that explore number mismatch effects in intervention configurations in the comprehension of object A’-dependencies, relative clauses and questions. The study capitalizes on the finding of object attraction in sentence production, in which speakers sometimes erroneously produce a verb that agrees in number with a plural object in object relative clauses. Evidence points to the role of three critical constructs from formal syntax: intervention, intermediate traces and c-command (Franck et al., 2010). Experiment 1, using a self-paced reading procedure on these grammatical structures, shows the enhancing effect of number mismatch in intervention configurations, with faster reading times with plural (mismatching) objects. Experiment 2, using an on-line grammaticality judgment task on the ungrammatical versions of these structures, shows an interference effect in the form of attraction, with slower response times with plural objects. Experiment 3 with a similar grammaticality judgment task shows stronger attraction from c-commanding than from preceding interveners. Overall, the data suggest that syntactic computations in performance refer to the same syntactic representations in production and comprehension, but that different tasks tap into different processes involved in parsing: whereas performance in self-paced reading reflects the intervention of the subject in the process of building an object A’-dependency, performance in grammaticality judgment reflects intervention of the object on the computation of the subject-verb agreement dependency. The latter shows the hallmarks of structure-dependent attraction effects in sentence production, in particular, a sensitivity to specific characteristics of hierarchical representations.